Relationship between electromagnetic and acoustic emissions in deformed piezoelectric media: Microcracking signals. (15th March 2015) - Mastrogiannis, D.; Antsygina, T.N.; Chishko, K.A.; Mavromatou, C.; Hadjicontis, V.
Abstract: Simultaneous acoustic (AE) and electromagnetic (EME) emissions during uniaxial compression of polycrystalline natural rocks which behave like brittle 'isotropic' piezoelectrics are studied experimentally. The plastic deformation of the brittle rocks is carried out mainly by microcracking which due to piezoelectric properties of the samples is accompanied by generation of electroacoustic waves. Such excitations can be interpreted as polarization currents and, consequently, as sources of electromagnetic fields that can be detected not only within the piezoelectric sample but also in its exterior. As a result, electromagnetic irradiation from deformed sample is accessible to be registered by an external antenna. The corresponding mechanism differs essentially from EME of moving dislocations in ionic crystals. We present the theoretical description of the electroacoustical irradiation during microcracking in isotropic piezoelectric plate. An agreement between theory and experiment has been discussed.